The Addition Effects of Glucose as a Co-substrate on Xylitol Production by Candida guilliermondii - Laksmi Ambarsari; Suryani Suryani; Steffanus Gozales; Puspa Julistia Puspita (IPB University, 2015)
High cost production is one of the constraints of the commercial xylitol production due to high energy needed and pure raw materials. Therefore, it is necessary to improve the xylitol production eficiently with lower production cost by using microorganisms. The research objectives were to determine the optimum xylitol production from xylose by metabolism of C. guilliermondii and effect of glucose as a co-substrate in fermentation medium. The ratio of glucose : xylose (g/L) was 1:25, 1:12, 1:5 and 1:2.5 respectively. The xylitol concentration was measured by spectrophotometer method (D-sorbytol/D-xylitol kit). The result showed that the exponential phase of Candida guilliermondii was 12 h to 36 of incubation and optimum of incubation time to produce the highest xylitol was 72 h. The best ratio- of glucose : xylose to produce xylitol was 9 g/L glucose : 45 g/L xylose (1 : 5). The xylitol concentration produced from medium with the addition of glucose was 2.85 g/L. This concentration increased five times compared to that in the medium without addition of glucose that only reached 2.85 g/L. According to this study, the addition of glucose as a co-substrate could increase the xylitol production.